The Misappropriation of the Haka: Are the Current Legal Protections around Mātauranga Māori in Aotearoa New Zealand Sufficient? - Wilson, Isabella Tekaumārua (Victoria University of Wellington Law Review, 2020)
This article analyses the protections the New Zealand intellectual property framework provides for the haka and mātauranga Māori. Part II of this article defines the key terms of "misappropriation", "traditional knowledge" and "mātauranga Māori" in order for the reader to fully understand these concepts in an indigenous, and specifically Māori, context. Part III of this article discusses the importance and significance of haka in Māori culture, particularly looking at the history and significance of Ka Mate, the most well-known haka in New Zealand and the world. Examples of different companies, both New Zealand and internationally-owned, using the haka for commercial benefit are analysed to establish whether or not their use of the haka is misappropriation, and if so, the harm this misappropriation has caused Māori. Part IV discusses the current legal protections New Zealand provides for mātauranga Māori and whether they sufficiently protect the haka and mātauranga Māori generally. It will assess the Haka Ka Mate Attribution Act 2014 as a case study. Part V outlines the limitations of the intellectual framework. Part VI of this article looks to what legal protections would be sufficient to protect against the misappropriation of the haka and mātauranga Māori generally.